Respuesta :

9514 1404 393

Answer:

  (x, y) = (2, -1)

Step-by-step explanation:

A graphing calculator can find a solution quickly. (see attached)

__

The first equation can give an expression for y:

  y = 3x -7

We can substitute this into the second equation:

  2x +3(3x -7) = 1

  11x -21 = 1 . . . . . . simplify

  11x = 22 . . . . . . . add 21

  x = 2 . . . . . . . divide by 2

  y = 3(2) -7 = -1 . . . . using our equation for y

The solution is (x, y) = (2, -1).

Ver imagen sqdancefan